Quantification of heavy metals in canned tomato paste sold in Ubani-Umuahia, Nigeria - Uroko, RI; Okpashi, VE; Etim, NE; Fidelia, AC (Journal of Bio-Science, 2019)
In recent years there has been an increase in the contaminations of heavy metals on the environment. Government and private organization have shown their interest in the effect of dietary exposure to several heavy metals. These heavy metals have been implicated in the etiology of many diseases with high risk to humans. Canned tomatoes paste is one of the important health deterioting factors to human health in Ubani-Umuahia, Nigeria. In this study atomic absorption spectrophotometer was used to screen for nine heavy metals concentration in ten different brands of canned tomatoes paste sold at Ubani-Umuahia market in Nigeria. Human risk assessment was calculated using the collated data to evaluate the predictive risk of human health after the consumption of canned tomatoes paste. Results shows that lead and nickel were not detected in all the canned tomatoes. In comparison low concentrations of copper, iron, and manganese were notated but high concentrations of chromium and cadmium were detected in all the tested tomatoes pastes. Cobalt and zinc concentration was notated lower than permissible limit. The daily intake of copper, cobalt, manganese, chromium, cadmium, nickel, iron, zinc and lead were below their tolerable values in canned tomatoes. The predicted lifetime for carcinogens to occur was less than one (<1). Copper, cobalt, iron, and zinc were below the acceptable value for non-cancer risk with HQ <1.The risk of incurring cancer by ingesting canned tomatoes was within the lifetime predicted a range of (1.0E-6 to 1.0E-4). Finds suggest that prolong and persistent consumption of these heavy metals may cause toxicity and consequential heath challenges. J. bio-sci. 28: 1-11, 2020